Odpowiedź :
Odpowiedź:
[tex]a)\\\\+\begin{cases}4x+y=5\\2x-y=-2\end{cases}\\--------\\6x=3\ \ /:6\\\\x=\frac{3}{6}\\\\x=\frac{1}{2}\\\\\not4^2\cdot\frac{1}{\not2_{2}}+y=5\\\\2+y=5\\\\y=5-2\\\\y=3\\\\\begin{cases}x=\frac{1}{2}\\y=3\end{cases}[/tex]
[tex]b)\\\\+\begin{cases}2x+3y=5\\-2x+y=-1\end{cases}\\---------\\4y=4\ \ /:4\\y=1\\\\\\2x+3\cdot1=5\\\\2x+3=5\\\\2x=5-3\\\\2x=2\ \ /:2\\\\x=1\\\\\begin{cases}x=1\\y=1\end{cases}\\\\\\c)\\\\+\begin{cases}5x-3y=1\\-5x+y=9\end{cases}\\--------\\-2y=10\ \ /:(-2)\\y=-5\\\\\\5x-3\cdot(-5)=1\\\\5x+15=1\\\\5x=1-15\\\\5x=-14\ \ /:5\\\\x=-\frac{14}{5}\\\\\begin{cases}x=-\frac{14}{5}\\y=-5\end{cases}[/tex]